2013
DOI: 10.1097/sap.0b013e3182586fac
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hatchet-Shaped Tensor Fascia Lata Flap and Pedicle Anterior Lateral Thigh Flap for Treatment of Trochanteric Sores

Abstract: The pedicle ALT flap is a more effective treatment than the TFL flap for the surgical management of trochanteric sores. The hatchet-shaped TFL flap should be reserved for the reconstruction of recurrent trochanteric sores or for use in the critically ill patient who cannot tolerate longer anesthesia and operation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity . Li et al reported that pALT flaps have a lower recurrence rate but require a longer operative time and prolonged anaesthesia than hatchet‐shaped TFL flaps for the surgical management of trochanteric sores. Consequently, in treating trochanteric pressure sores, we preferred to utilise hatchet‐shaped TFL flaps for a smaller defect and pALT flaps for a larger defect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity . Li et al reported that pALT flaps have a lower recurrence rate but require a longer operative time and prolonged anaesthesia than hatchet‐shaped TFL flaps for the surgical management of trochanteric sores. Consequently, in treating trochanteric pressure sores, we preferred to utilise hatchet‐shaped TFL flaps for a smaller defect and pALT flaps for a larger defect.…”
Section: Discussionmentioning
confidence: 97%
“…According to Wang et al and our previous studies, the modified design of the pALT myocutaneous flap without skeletonisation of perforators is reliable and easily harvested for the reconstruction of trochanteric and ischium pressure sores with limited morbidity. 13,15,16 Li et al 17 reported that pALT flaps have a lower recurrence rate but require a longer FIGURE 2 An 83-year-old woman with multiple pressure sores. A, B, C, 12 cm × 16 cm sacral pressure sore, 8 cm × 5 cm right trochanteric pressure sore, and 3 cm × 3 cm left trochanteric pressure sore, respectively; D, left trochanteric pressure sores treated with delayed primary closure; E, right trochanteric defect covered with hatchet-shaped tensor fascia lata flap; F, planning of SGAP flap for sacrum defect; G, appearance of elevated f lap; and H, I, postoperative result 8 weeks after the surgery operative time and prolonged anaesthesia than hatchetshaped TFL flaps for the surgical management of trochanteric sores.…”
Section: Discussionmentioning
confidence: 99%
“…The TFL flap can be designed with a hatchet-shaped incision to provide more well-vascularized muscle to fill the wound defect, or combined with tangential splitting of the vastus lateralis to increase flap distance (13)(14)(15). Another commonly used flap for trochanteric reconstruction is the pedicled ALT flap, which has lower rates of ulcer recurrence compared to the hatchet-shaped TFL flap (16).…”
Section: Reconstructive Considerationsmentioning
confidence: 99%
“…44 ►Table 4 describes other LE functional measures described by four studies, including limitation of motion, joint stiffness, function recovery, and mean time to return to baseline function. 7,32,44,47 Only two studies described the weight-bearing status of patients separately from ambulatory status (►Table 3). 14, 54 Yang et al reported full weight-bearing status in all 15 patients, while Lu et al described time to weight-bearing; in their diabetic foot ulcer patient population, the time to initial weight bearing was an average of 2 AE 1.3 months, and time to full weight bearing was an average of 3 AE 1.5 months after FTT.…”
Section: Functional Outcomesmentioning
confidence: 99%